THE EFFECT OF âGISTâ AND LEARNING STYLE TOWARD READING COMPREHENSION OF GRADE XI STUDENTS AT SMA DWIJENDRA BUALU IN ACADEMIC YEAR 2011/2012 - PUSPAYANI S. PUTRI, AYU DIAN (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Dian Puspayani S.Putri, Ayu, 2012, The Effect of Gist and Learning Style on Reading Comprehension of Grade XI Students at SMA Dwijendra Bualu in Academic Year 2011/2012, Post Graduate Program, Ganesha University of Education. This master thesis has been revised and approved by: Advisor 1. Prof. Dr. I Ketut Seken, M.A., Advisor 2. Prof. Dr. Nyoman Padmadewi, M.A. Key words: GIST, learning style, reading comprehension, conventional reading technique This study concerned with experimental research which investigated whether or not there is any effect of Generating Interaction between Schemata and Text (GIST) and learning style on reading comprehension, and to investigate the relationship between the use of GIST, conventional reading technique and learning style. This study was carried out in SMA Dwijendra Bualu on grade XI students through a 2X4 true-experimental research design where the participants were homogenously The students in experimental group were taught using GIST while the students in control group were taught using conventional reading technique. Each group consisted of students with visual, aural, read-write, kinesthetic learning style. Therefore, there were eight groups altogether; students who were taught using GIST with visual learning style, students who were taught using conventional reading technique with visual learning style, students who were taught using GIST with aural learning style, students who were taught using conventional reading technique aural learning style. students who were taught using GIST with read-write learning style, students who were taught using conventional reading technique with read-write learning style, students who were taught using GIST with kinesthetic learning style, and students who were taught using conventional reading technique kinesthetic learning style. Post-tests were administered to all groups after the twelfth meeting. A two-way ANOVA test indicated that the experimental group students who were taught using GIST outperformed the group of students who were taught using the conventional reading technique. However, two-way ANOVA test could not answered the significance of average data in this 2x4 factorial design. Therefore, it was needed to use post-hoc or multiple comparison test to show the interaction from each cell of the data in this study.